The Effect of Contrast Training Method on Increasing of Vertical Jump, Speed, and Agility in 3x3 Basketball Athletes - Wendi Rahmattulloh; Dede Rohmat Nurjaya; Masayu Rizka Risjanna (Universitas Negeri Semarang, 2025)
The purpose of this study was to investigate the effect of contrast training method on increasing of vertical jump, speed and agility in 3x3 basketball athletes. The method used in this study was an experimental method with a Pretest Posttest Design research design. The study population consisted of 13 3x3 basketball athletes from Bandung City: 6 male athletes and 7 female athletes in preparation for PORPROV 2026. Who were also the research sample, selected using a total sampling technique. The instrument used in this study was vertical jump test, sprint 20 meter test and lane agility test. Data analysis was conducted using the paired sample T-Test statistical test with the aid of the SPSS version 25 application. The results showed tha there was a significant effect (p < .001) on improving vertical jump, speed, and agility in 3x3 basketball athletes. This study also concludes that there was no significant difference in the effect (p > .05) of this training method's application between the male and female athlete groups. Thus, contrast training proved to be an effective and recommended training method for enhancing crucial physical components (explosive power) equally for 3x3 basketball athletes, regardless of gender.